Judicial Independence and Political Influence in Modern Democracies - Fathya, Adinda Zahra; Santika, Rani (Journal of Law and Social Politics, 2025)
This research examines contemporary human rights violations and evaluates the effectiveness of international legal mechanisms in addressing these issues. Using a qualitative approach, it employs doctrinal legal analysis and case studies to assess the role of international courts, tribunals, and human rights organizations. Key legal instruments, including the Universal Declaration of Human Rights, the Geneva Conventions, and the Rome Statute, are analyzed to understand their impact on prosecuting war crimes, crimes against humanity, and genocide. Reports from the United Nations, the International Criminal Court (ICC), and regional human rights bodies highlight enforcement challenges, such as political constraints, jurisdictional limitations, and state non-cooperation. Case studies on Ukraine, Myanmar, Ethiopia, and Venezuela illustrate both the successes and shortcomings of international legal interventions. Strengthening global accountability requires enhanced cooperation, judicial independence, and more effective sanction mechanisms. The study also explores judicial independence as a fundamental pillar of democracy, assessing the extent of political influence on judicial autonomy. Through content analysis of judicial reforms and constitutional changes in democratic nations, the research identifies key patterns of political interference, including judicial appointments, budgetary control, and legislative restrictions on judicial review. While judicial independence upholds constitutional integrity and civil liberties, political interference can erode democratic institutions. The study concludes that safeguarding judicial autonomy necessitates strong legal frameworks, institutional transparency, and active civil society participation. These findings contribute to legal and political discourse, offering policy recommendations to enhance judicial resilience and democratic governance.